Proceedings of SPE Annual Technical Conference and Exhibition 2003
DOI: 10.2523/84122-ms
|View full text |Cite
|
Sign up to set email alerts
|

Improvement Processes for Coalbed Natural Gas Completion and Stimulation

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractDrilling activity to access natural gas production from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…These include: (i) how best to address, in a numerically efficient and physically realistic manner, the handling of layer debonding and fluid invasion along layer interfaces with associated stunting of fracture height growth in shallower wells-relatively limited progress has been made in this area [94][95][96]; (ii) how to appropriately adjust current (linear elastic) simulators to enable modeling of the propagation of hydraulic fractures in highly cleated coal bed seams (for the extraction of methane) [97]; (iii) how to appropriately adjust current (linear elastic) simulators to enable modeling of the propagation of hydraulic fractures in weakly consolidated and unconsolidated ''soft'' sandstones, such as are found in the Gulf of Mexico-limited progress has been made in this area [98,99]; (iv) laboratory and field observations demonstrate that mode III fracture growth does occur [100], and this needs to be further researched; (v) related to (iii), the effect of the invaded zone ahead of the fracture tip needs to be further researched-a criterion to switch from a fluid lag based approach to an invaded zone based approach in a numerical model is required; (vi) suitable models for the propagation of hydraulic fractures in naturally fractured reservoirs that result in complex (non-planar) geometric configurations requires development [101]; and (vii) how to efficiently model 3D or ''out of plane'' effects, such as fracture re-alignment (when the fracture initiates following an orientation that is not perpendicular to the minimum in situ stress and then tries to re-align itself), which could be a cause of near-wellbore tortuosity or even ''pinching,'' a factor that usually determines the success or failure of hydraulic fracturing treatments [102].…”
Section: Discussionmentioning
confidence: 99%
“…These include: (i) how best to address, in a numerically efficient and physically realistic manner, the handling of layer debonding and fluid invasion along layer interfaces with associated stunting of fracture height growth in shallower wells-relatively limited progress has been made in this area [94][95][96]; (ii) how to appropriately adjust current (linear elastic) simulators to enable modeling of the propagation of hydraulic fractures in highly cleated coal bed seams (for the extraction of methane) [97]; (iii) how to appropriately adjust current (linear elastic) simulators to enable modeling of the propagation of hydraulic fractures in weakly consolidated and unconsolidated ''soft'' sandstones, such as are found in the Gulf of Mexico-limited progress has been made in this area [98,99]; (iv) laboratory and field observations demonstrate that mode III fracture growth does occur [100], and this needs to be further researched; (v) related to (iii), the effect of the invaded zone ahead of the fracture tip needs to be further researched-a criterion to switch from a fluid lag based approach to an invaded zone based approach in a numerical model is required; (vi) suitable models for the propagation of hydraulic fractures in naturally fractured reservoirs that result in complex (non-planar) geometric configurations requires development [101]; and (vii) how to efficiently model 3D or ''out of plane'' effects, such as fracture re-alignment (when the fracture initiates following an orientation that is not perpendicular to the minimum in situ stress and then tries to re-align itself), which could be a cause of near-wellbore tortuosity or even ''pinching,'' a factor that usually determines the success or failure of hydraulic fracturing treatments [102].…”
Section: Discussionmentioning
confidence: 99%
“…The face cleat is more continuous and connected, while the butt cleat is discontinuous and terminates at face cleats (Laubach et al ., ; Moore, ). Therefore, face cleats are more significant for fluid flow, and result in permeability anisotropy in coals (Koenig, , ; Ayers, ; Massarotto et al ., ; Olsen et al ., ; Titheridge, ). Numerous studies have shown that fractures that are aligned parallel or within 30° to S Hmax orientation enhance fluid flow (e.g.…”
Section: Implications For Hydrocarbon Exploration and Productionmentioning
confidence: 99%
“…The C‐M Basin is a major coal mining region and is of significant interest for coal seam gas production in eastern Australia. Coal seams are self‐sourcing reservoirs with low matrix permeability (Ayers, ), and thus the natural fracture system of coal (coal cleats) plays a critical role in hydrocarbon production (Laubach et al ., ; Ayers, ; Olsen et al ., ; Bell, ). Coal cleats are opening‐mode fractures, usually sub‐vertical, and form systematically in two perpendicular sets, namely face cleat and butt cleat (Laubach et al ., ; Moore, ).…”
Section: Implications For Hydrocarbon Exploration and Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, much effort has been spent in the area of completion design, fluid chemistry, proppant selection and job procedures in an effort to optimize our understanding of stimulation behavior in coal bed environments. [2][3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 98%